Neuro-metabolite profiles of rodent models of psychiatric dysfunctions characterised by MR spectroscopy. (1st March 2019) - Sekar, Sakthivel; Grandjean, Joanes; Garnell, Joanne FV.; Willems, Roland; Duytschaever, Hilde; Seramani, Sankar; Su, Huang; Ver Donck, Luc; Bhakoo, Kishore K.
Abstract: Neuroimaging endophenotypes in animal models provide an objective and translationally-relevant alternative to cognitive/behavioral traits in human psychopathologies. Metabolic alterations, such as those involved in the glutamate-cycle, have been proposed to play a preponderant role in both depression and schizophrenia. Chronic Mild Unpredictable Stress (CMUS) and sub-chronic administration of NMDA receptor antagonist generate animal models of depression and schizophrenia, respectively. The models are based on etiologically-relevant factors related to the induction and support of these psychopathologies. To test metabolic alterations within the glutamate-cycle and in other major neurochemicals, single-voxel Magnetic Resonance Spectroscopy was recorded within the hippocampus in both rat models and control animals. Surprisingly, altered glutamate-related metabolites were observed in the CMUS model, but not NMDA-based model, as indicated by decreased glutamine and increased GABA levels. However, both models presented elevated total visible choline and inositol levels relative to controls. These results indicate the presence cell membrane metabolic alterations and inflammatory processes shared in both models, comparable to evidence presented in schizophrenia and depression and other comparable animal models. These translationally-relevant biomarkers may thus form the basis for drug-development targets in both psychopathologies. Highlights: SVS-MRS in rodent models of psychopathologies reveals relevant metabolic phenotype. Glutamine was decrease, with a increase in GABA level in CMUS model. Elevated Inositol and Choline concentrations in both CMUS and NMDA models.